Government Size and Economic Growth. An analysis between China and India. - Sibt-e-Ali, Muhammad; Hussain, Dr. Tariq; Mazhar, Fatima; Khan, Irfan Hussain; Parveen, Sabiha (The journal of contemporary issues in business and government, 2021)
Over the period from 1961 to 2018, a new Smooth Transition Autoregressive model was used to examine how the size of the government affected GDP growth in India and China. Economic growth and government size appear to have a strong and positive correlation. In other words, as these countries' governments expand, so does their economies. China's government size is unlikely to have a greater impact on economic growth than India's, based on the findings. Economic growth is positively and significantly affected by both China's and India's government sizes. China's government size had a larger effect, but India's was also highly significant. Finally, it makes no recommendations for reducing government spending. The issue is one of resource allocation. Crowding-out impacts and costs result from poor resource allocation.